Evaluasi Tingkat Keberhasilan Pembelajaran Online dengan menggunakan Metode Fuzzy Mamdani - Ismail; Sakina (Universitas Sulawesi Barat, 2022)
Online learning is no longer a new thing for many schools today, online learning is a solution for schools, teachers and students to continue to carry out teaching and learning activities even though they are separated by distance. With this solution, it is also necessary to have an evaluation process to measure whether this method is really successful and feasible to use. SMK Negeri 1 Tapalang Barat is a school that still applies online learning to this day because the school building is still under renovation. However, the evaluation process of the learning process has never been carried out, departing from these problems, this study discusses the evaluation of the success rate of online learning using the Mamdani fuzzy method. The test subjects in this study were students of class XII Teknik Audio Video at SMK Negeri 1 Tapalang Barat, whose data were taken from school archives and the distribution of questionnaires to students and teacher responses to the evaluation system of online learning success rates were collected through questionnaires. The data that has been collected will be analyzed using a quantitative approach. The results showed that the system built to facilitate the school in evaluating student learning in online learning for class XII Teknik Audio Video at SMK Negeri 1 Tapalang Barat has been successfully tested and runs according to its functionality and has succeeded in meeting the needs of the school for the problems faced, both from the point of view of the authors and users who use the system, as well as the manual calculation of the mamdani fuzzy method has been successfully applied to the system.